2022
DOI: 10.34123/icdsos.v2021i1.229
|View full text |Cite
|
Sign up to set email alerts
|

An insight into Youth Unemployment in Indonesia

Abstract: Youth unemployment in Indonesia has continued to remain at a high level relative to other age categories for several years. The case of Indonesia’s youth unemployment is grave with the presence of a low workforce participation rate, informal employment, and higher unemployment rates in young people compared with adults. Due to the lack of research on a country-wise view of youth unemployment, this study focuses on providing a much better understanding of the youth unemployment problem in emerging countries, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…The articles presented in this research reveal various aspects related to labor reform in Indonesia. Topics studied include labor market evaluation (Bradley & Kügler, 2019), primary care doctor satisfaction (Maharani et al, 2019), determinants of worker poverty (Faharuddin & Endrawati, 2022), foreign direct investment (Suryanta & Patunru, 2022), youth unemployment (Yanindah, 2022), and the relationship between employment and married women's labor force participation (Rimkute & Sugiharti, 2022). These findings provide insight into the dynamics and challenges surrounding labor reform in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The articles presented in this research reveal various aspects related to labor reform in Indonesia. Topics studied include labor market evaluation (Bradley & Kügler, 2019), primary care doctor satisfaction (Maharani et al, 2019), determinants of worker poverty (Faharuddin & Endrawati, 2022), foreign direct investment (Suryanta & Patunru, 2022), youth unemployment (Yanindah, 2022), and the relationship between employment and married women's labor force participation (Rimkute & Sugiharti, 2022). These findings provide insight into the dynamics and challenges surrounding labor reform in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…The determinants of worker poverty (Faharuddin & Endrawati, 2022) and foreign direct investment (Suryanta & Patunru, 2022) provide important insights into the economic factors that influence the dynamics of employment and investment in Indonesia. Handling youth unemployment (Yanindah, 2022) requires targeted interventions and policies. The relationship between employment and labor force participation of married women (Rimkute & Sugiharti, 2022) highlights the importance of considering gender factors and the role of household technology in designing employment policies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of productivity of individuals is directly proportional to the length of time they have attended training (Simanjuntak, 1998). In Yanindah's (2021) research, it is revealed that individuals who take part in training have a better chance of getting a job. ILO (2004) states that individuals with no work experience reduce the chances of getting a job in the modern economic sector.…”
Section: Figure 3 Labor Market Equilibrium Curvementioning
confidence: 99%
“…However, finding work in their field of study in emerging cities in Indonesia also presents challenges. Increasingly tight competition in the labor market, especially in sectors relevant to higher education, can make new graduates feel pessimistic about finding suitable employment (Yanindah, 2021). This encourages some educated Indonesian youth to pursue higher education, such as a master's program, in the hope of enhancing their job opportunities.…”
Section: The Labor Market For Youthmentioning
confidence: 99%